Factors affecting students’ intentions toward green entrepreneurship in COVID-19 pandemic times: A case study of Egyptian universities - Hamed A. Ead; Ahmed Rashed; Waleed Ghoniem; Mohamed Turk (International Journal of Education and Learning, 2022)
The impact of government assistance, entrepreneurial self-efficacy, conceptual development support, and educational development support on green entrepreneurial aspirations through university curriculum during the COVID-19 epidemic is explored in this research. It is the first of its kind in Egypt and is based on a sample population of 502 undergraduate students from various faculties at five Egyptian universities (two public, two private, and one institution with international cooperation). It employs structural equation modelling via SmartPLS. This study can assist other Egyptian universities in creating strategic plans for environmental initiatives and ensuring that students are given the necessary skills to succeed. The study aims to evaluate the impact of conceptual development support offered by universities in terms of fostering interest and presenting novel ideas to students to start a new project, government support provided in terms of laws and programs to encourage entrepreneurship, development of university curriculum to promote entrepreneurial self-efficacy through regular courses, postgraduate practices, and networking with entrepreneurs. Academics, especially those in universities in Egypt or other Arab or African nations, as well as policymakers, can gain from this research's potential to build new standards to support green entrepreneurship and sustainable economies.